Simulação e desenvolvimento de receptor para energia solar concentrada - Maia, Elton Perceu Silva (2024)
A growing concern nowadays is the constant rise in the planet’s temperature due to the increase in greenhouse gas emissions in the atmosphere. Actions by governments and non-governmental institutions have been carried out, such as the creation of the Paris Agreement goals, which aim to limit this global temperature increase to 1.5 ◦C and reduce CO2 emissions to zero by mid-century. Despite the efforts made, the implementation of energy transition technologies is far from the levels needed to achieve the defined goals. Many countries are adopting concentrated solar power CSP as an alternative to non-renewable sources. Through research into new CSP technologies, it is possible to make it increasingly viable among the range of clean energy alternatives. Therefore, this work contributes by developing a solar receiver that aggregates the best characteristics already widely researched and advances in seeking the best efficiency. The aim is to computationally simulate the receiver using the ANSYS CFX software, with average Direct Normal Irradiance DNI values from the Northeast region of Brazil, in addition to specifying the construction of the solar receiver, which is part of a set formed by a parabolic dish and a support and movement structure. The simulated solar receiver achieved thermal capacity values of 2.4 kW for a mass flow rate of 0.002 kg/s and DNI of 800W/m2. For DNI values above 600W/m2, it is possible to reach steam reforming temperatures for green hydrogen production.